Investigation of wastewater quality at Griya Kain Tuan Kentang, Palembang, South Sumatra - Saputra, Muhammad Alif; Pusvita, Dwi; Hanifa, Atina Qurba; Sunarti, Riri Novita; Soleha, Siti; Saputra, Andi; Falahudin, Irham (Univeritas Papua, 2025)
Liquid waste from dyeing is the main source of pollution in small industrial areas such as Griya Kain Tuan Kentang, Palembang City, which is famous for its woven and jumputan fabric production. Liquid waste from these activities has the potential to pollute the surrounding environment. Therefore, it is important to evaluate its quality to support ecosystem sustainability and public health. This study aims to analyse the quality of wastewater using physical parameters (temperature, TDS, TSS and brightness), chemical parameters (pH, Cd, Pb, Fe, Cu), and biological (Coliform and Escherichia coli contamination). The type of research used is quantitative research with experimental methods and laboratory tests. Samples from three locations were analysed in the integrated laboratory of UIN Raden Fatah Palembang and directly analysed on site for physical parameters (temperature, TDS and brightness), biological parameters were analysed using the MPN (Most Probable Number) method, and chemical parameters for heavy metals using AAS (Atomic Absorption Spectroscopy). The results of this study provide an overview of the quality of wastewater at Griya Kain Tuan Kentang which has not met the wastewater quality standards according to the Regulation of the Minister of Environment in 2016 for the brightness and TDS parameters at locations 1 and 2 have met the wastewater quality standards, at location 3 the brightness parameters have not met the wastewater quality standards.